Optimal-Enhanced Solar Cell Ultra-thinning with Broadband Nanophotonic Light Capture - Mendes, Manuel J. (2018)
Action FP7-PEOPLE-2013-IEF through the DIELECTRIC PV project (Grant 629370). Grant SFRH/BPD/115566/2016. Grant SFRH/BPD/114833/2016.